2023
DOI: 10.3390/healthcare12010015
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Digital Addiction on Brain Function and Structure of Children and Adolescents: A Scoping Review

Keya Ding,
Yining Shen,
Qianming Liu
et al.

Abstract: The escalating prevalence of studies investigating digital addiction (DA) and its detrimental impact on the human brain’s structure and functionality has been noticeable in recent years. Yet, an overwhelming majority of these reviews have been predominantly geared towards samples comprising college students or adults and have only inspected a single variant of DA, such as internet gaming disorder, internet addiction disorder, problematic smartphone use, tablet overuse, and so forth. Reviews focusing on young c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 87 publications
(214 reference statements)
0
3
0
Order By: Relevance
“…Structural equation modeling unveiled that prosocial behavior tends to diminish as electronic media use escalates. This phenomenon may be attributed to the pervasive nature of electronic media, which, as documented by Ding et al, is becoming a significant health concern globally, increasingly affecting younger populations [ 76 ]. The World Health Organization, in the 11th edition of the International Classification of Diseases (ICD) published in 2018, has recognized video game addiction as a mental health disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural equation modeling unveiled that prosocial behavior tends to diminish as electronic media use escalates. This phenomenon may be attributed to the pervasive nature of electronic media, which, as documented by Ding et al, is becoming a significant health concern globally, increasingly affecting younger populations [ 76 ]. The World Health Organization, in the 11th edition of the International Classification of Diseases (ICD) published in 2018, has recognized video game addiction as a mental health disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization, in the 11th edition of the International Classification of Diseases (ICD) published in 2018, has recognized video game addiction as a mental health disorder. Children, with their developmental cognitive and neural mechanisms, are particularly vulnerable to the adverse impacts of electronic media [ 23 , 76 ]. Excessive engagement with electronic media may disrupt crucial real-life interactions that foster the development of communication skills and prosocial behaviors such as empathy, sharing, and cooperation [ 22 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also found that intervention programs significantly reduced digital addiction symptoms, depression and anxiety levels, and further studies with prevention programs are needed [12]. Ding et al (2024) stated in another study that it would be more beneficial for parents to spend more face-to-face time with their children by reducing the use of digital tools outside working hours [13].…”
Section: Introductionmentioning
confidence: 99%